Investigation of stress corrosion cracking behavior of super 13Cr tubing by full-scale tubular goods corrosion test system. (April 2015) - Lei, X.W.; Feng, Y.R.; Fu, A.Q.; Zhang, J.X.; Bai, Z.Q.; Yin, C.X.; Lu, C.H.
Highlights: A full-scale tubular goods corrosion test system was built. High temperature–pressure–stress corrosion experiment was carried out on the system. Stress corrosion cracking took place and the failure behavior of super 13Cr was investigated. Interesting "X" shape crack features were found, and fracture evolution process was discussed. Abstract: In this paper, a self-built device called "full-scale tubular goods corrosion test system" was used to test a 6 m length super 13Cr tubing (with coupling) to study its corrosion performance in spent acid. The specimen fractured at the tubing and was investigated by visual inspection, optical microscopy (OM), scanning electron microscopy (SEM), energy dispersive spectrometer (EDS), and mechanical test. It was the joint function of tensile force (78.6% actual yield strength), inner pressure (70 Mpa) and spent acid that induced stress corrosion cracking (SCC) of the tubing at 120 °C. Three different areas were found on the fracture surface, including crack initiation area, crack expansion area, and final fracture area. The fracture initiated from the "X" shape corrosion cracks which were evolved from small corrosion pits. The reduction of ductility and toughness may also facilitate SCC of the tubing.